2014
DOI: 10.1007/s11738-014-1524-x
|View full text |Cite
|
Sign up to set email alerts
|

Participation of GA3, ethylene, NO and HCN in germination of Amaranthus retroflexus L. seeds with various dormancy levels

Abstract: Amaranthus retroflexus seeds were dormant at 25°C in the darkness and in the light, and also at 35°C in the darkness. GA 3 and ethylene partially removed dormancy at 35°C in the darkness and at 25°C in the light. Dormancy was removed by 1-5 days of treatment with nitric oxide or cyanide. The effect of NO and HCN was inhibited by cPTIO, thus the effect of HCN was NO dependent. Dry storage for 16 weeks could partially release dormancy only at 35°C, but not at 25°C. Dry storage increased the response to light, GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 34 publications
5
18
0
Order By: Relevance
“…In addition to hormones, such as gibberellins and ethylene, nitrogen-containing compounds, such as nitrates, nitrites, hydroxylamines, and azides, can also break dormancy in seeds, and it was suggested that the response of seeds to nitrogenous compounds was caused by NO (Hendriks and Taylorson 1974). NO from various donors, such as nitroprusside (SNP), S-nitroso-N-acetylpenicillamine (SNAP), S-nitrosoglutathione (GSNO), and acidified KNO 2 , removes dormancy in apple, Arabidopsis, barley, lettuce, and redroot pigweed seeds (Beligni and Lamattina 2000;Bethke et al 2004;Gniazdowska et al 2010;Liu et al 2011;Kępczyński and Sznigir 2014). NO produced by seeds is now recognized as a signaling molecule involved in regulating germination of dormant and non-dormant seeds in cooperation with plant hormones (Arc et al 2013b;Krasuska et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to hormones, such as gibberellins and ethylene, nitrogen-containing compounds, such as nitrates, nitrites, hydroxylamines, and azides, can also break dormancy in seeds, and it was suggested that the response of seeds to nitrogenous compounds was caused by NO (Hendriks and Taylorson 1974). NO from various donors, such as nitroprusside (SNP), S-nitroso-N-acetylpenicillamine (SNAP), S-nitrosoglutathione (GSNO), and acidified KNO 2 , removes dormancy in apple, Arabidopsis, barley, lettuce, and redroot pigweed seeds (Beligni and Lamattina 2000;Bethke et al 2004;Gniazdowska et al 2010;Liu et al 2011;Kępczyński and Sznigir 2014). NO produced by seeds is now recognized as a signaling molecule involved in regulating germination of dormant and non-dormant seeds in cooperation with plant hormones (Arc et al 2013b;Krasuska et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A. retroflexus seeds express relative dormancy and therefore germinate completely after harvest at relatively high temperatures, usually 35-40 s C (Kępczyński et al 1996;Liu et al 2011), but do not germinate at lower temperatures until their dormancy is interrupted. There are A. retroflexus seeds which are unable to germinate after harvest or germinated only partially at 35 s C (Schönbeck and Egley 1980;Kępczyński and Sznigir 2014), indicating that the level of dormancy depends on the harvest. A. retroflexus seed dormancy can be removed by dry storage, the effect which depends on the duration and temperature of storage (Schönbeck and Egley 1980;Kępczyński and Sznigir 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously found that exogenous NO stimulates germination of dormant Arabidopsis (Bethke et al 2004; Libourel et al 2006) and A. retroflexus seeds (Kępczyński and Sznigir 2014; Kępczyński et al 2017), indicating penetration of cells by NO. To confirm that FCM measures the NO level, embryos and leaves were treated with exogenous NO released from an acidified KNO 2 (Yamasaki 2000), at a concentration which was previously used to treat A. retroflexus seeds to increase the level of the compound in cells (Kępczyński et al 2017).…”
Section: Discussionmentioning
confidence: 93%
“…Recently the release of redroot pigweed (Amaranthus retroflexus L.) seeds dormancy was also observed in the light in the presence of NO. Light condition of redroot pigweed seed germination enhanced tissues response to phytohormones such as GA or ethylene but not to NO (Kępczyński and Sznigir 2014).…”
Section: Introductionmentioning
confidence: 89%